2017
DOI: 10.1159/000457947
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping, Platelet Activation, and Cardiovascular Outcome in Patients after Percutaneous Coronary Intervention: Two Pieces of the Puzzle of Clopidogrel Resistance

Abstract: Objectives: Individual platelet responses to antiplatelet therapy depend on genetic, cellular, and clinical factors. CYP2C19 and P2Y12 receptor polymorphisms are implicated in platelet responses to antiplatelet treatment. We aimed to evaluate the impact of CYP2C19 and C34T P2Y12 genotyping on platelet reactivity and cardiovascular outcome in patients after percutaneous coronary intervention (PCI) on clopidogrel treatment. Methods: We enrolled 408 patients with stable coronary artery disease (CAD) receiving asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
(36 reference statements)
0
6
0
Order By: Relevance
“…These findings were comparable to the findings of other studies. 7,8 Additionally, this study illustrated a significantly higher hemoglobin level among the smoking participants when compared to the non-smoking patients, although Yun Gi Kim and his team found evidence that the AUC measured by Multiplate Analyzer was not affected by hemoglobin level. 9 While there was a significantly lower AUC among the smoker participants as compared to the non-smoker in both study groups, these results are consistent with 5,10 and contrary to results by Kim et al, 2016.…”
Section: Discussionmentioning
confidence: 63%
“…These findings were comparable to the findings of other studies. 7,8 Additionally, this study illustrated a significantly higher hemoglobin level among the smoking participants when compared to the non-smoking patients, although Yun Gi Kim and his team found evidence that the AUC measured by Multiplate Analyzer was not affected by hemoglobin level. 9 While there was a significantly lower AUC among the smoker participants as compared to the non-smoker in both study groups, these results are consistent with 5,10 and contrary to results by Kim et al, 2016.…”
Section: Discussionmentioning
confidence: 63%
“…In some reports, HTPR in response to clopidogrel therapy affected up to 40% of treated individuals [ 9 , 94 , 95 ]. Of importance, the HTPR independently associated with larger intracoronary thrombus burden, worse post-PCI myocardial flow and perfusion, higher ischemic risk, and frequency of adverse cardiovascular outcomes such as stent thrombosis, myocardial infarction, stroke, and death in several studies on platelet aggregation, and therefore carries a poor prognosis in patients with ACS treated with clopidogrel after PCI [ 25 , 96 , 97 , 98 , 99 , 100 ]. HTPR can be partially overcome by assuring loading of clopidogrel prior to PCI, with administration of the higher dose (600 mg, compared to 300 mg) [ 101 , 102 ].…”
Section: Pharmacogenomics Eramentioning
confidence: 99%
“…For example, a genome-wide association study followed by CYP2C*2 genotyping in patients undergoing PCI suggested a link between the CYP2C*2 genotype and both diminished platelet response to clopidogrel (accounting for 12% of interindividual variation) and cardiovascular ischemic events or death during 1 year of follow-up (hazard ratio 2.42, p = 0.02) [ 26 ]. In another study, individuals carrying the CYP2C19*2 variant allele exhibited a 3-fold increased risk for adverse ischemic cardiovascular events on clopidogrel therapy [ 32 , 100 ]. Notably, this association is more prominent during the first year after PCI, and thereafter decreases significantly [ 113 ].…”
Section: Pharmacogenomics Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 434 articles (238 irrelevant studies, 119 reviews, 8 conference papers, 59 studies without adverse events, 4 animal trials, 4 case reports, and 2 non-English-language study) were excluded by title and abstract screening. Then, six studies [14][15][16][17][18] with incomplete data, one study [19] with incorrect data, one study [20] with a followup < 3 months and one study [21] without full-text were excluded respectively. Fifteen studies [8,9,[22][23][24][25][26][27][28][29][30][31][32][33][34] met the inclusion criteria.…”
Section: Study Characteristicsmentioning
confidence: 99%